The Internet as a marriage middleman: New patterns of love affairs in XXI century - Petrović, Dalibor; Pejković, Kristina (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2022)
The basic assumption of this paper is that the Internet has taken on a "matchmaking role" in creating emotional and marital relationships that are determinated with matching algorithms on the one hand, and virtual dating on the other. Therefore, our goal is to examine the basic social factors that contributed to the Internet's role in this regard. Accordingly, we will consider the potential consequences of such a transformation. First, we will analyze broader social processes that lead to the extraction of people from primary and direct relationships and to their re-rooting with the help of technological intermediaries. In this way, new communities based on the network principle are re-created, with the consequences of the building of friendly and emotional relationships. A revolutionary change of Internet technology is the possibility of making close connections with people who did not know each other before. In this regard, we will analyze the circumstances that led to the sphere of intimate relations becoming the most technologically mediated social sphere in the 21st century, because the Internet has become an irreplaceable, possible sovereign mddleman of love affairs. The conclusion is that algorithms, not the "game of fate", will determine who will produce offspring with whom, in the future.